If fibromyalgia did not exist, we should have invented it. A short history of a controversial syndrome - S. Perrot (PAGEPress Publications, 2012)
Fibromyalgia is a recent disease, and some physicians remain doubtful about its reality. The history of fibromyalgia is a story of controversies: the fight between subjectivity and cartesianism, and between old mind and body concepts. Fibromyalgia represents the emblematic condition of unexplained medical symptoms, far from well-defined diseases with objective biomarkers. In this review we will follow the fibromyalgia story along the ages and sciences to better understand this complex pain disorder, between soma and psyche, and between medicine and psycho-sociology and to demonstrate that fibromyalgia exist, we have not invented it.